Cluster headache is associated with unhealthy lifestyle and lifestyle-related comorbid diseases: Results from the Danish Cluster Headache Survey - Lund, Nunu; Petersen, Anja; Snoer, Agneta; Jensen, Rigmor H; Barloese, Mads (Cephalalgia, 2019)
Aim To compare the prevalence of unhealthy lifestyle factors and comorbid disorders in cluster headache patients with headache-free controls, in order to discuss pathophysiology and possible consequences. Methods Cluster headache patients from the Danish cluster headache survey aged 18–65 years, diagnosed according to ICHD-II, were compared to sex- and age-matched headache-free controls. Participants completed questionnaires and structured interviews. Results A total of 400 cluster headache patients and 200 controls participated. Patients had a more unhealthy lifestyle compared with controls in the form of current and current/former smoking (48.3% vs. 9.0%, p < 0.001 and 74.5% vs. 30.0%, p < 0.001, respectively), higher average alcohol intake per week (98.2 grams vs. 77.9 grams, p = 0.033) and BMI (26.1 vs. 24.2 kg/m2, p < 0.001), whereas coffee and energy drink consumption was equally distributed. Further, lifestyle-related, psychiatric and pain-related diseases were much more prevalent in patients compared with controls, except for diabetes. Sub-group analyses revealed that current/former smokers had a worse clinical presentation than never smokers. Conclusion Unhealthy lifestyle factors and lifestyle-related diseases were more prevalent in cluster headache patients compared to controls. As lifestyle-related diseases might have serious consequences in the management of cluster headache, it is key to inform patients at an early time point about the possible risks of their lifestyle choices.